DIVERSITY OF PROBIOTIC BACTERIAL LECTIN SYSTEMS - M. V. Lakhtin; V. M. Lakhtin; S. S. Afanasiev; V. A. Aleshkin (Acta Biomedica Scientifica)
Lectin systems of industrial strains of probiotic bacteria of human origin were investigated. Lectin systems were observed as ceil surface and extracellular; solubilized in mild and firm conditions; solid phased fluorescent and chemiluminescent; anionic/acidic, neutral and cationic/alkaline; masked/biocked/encapsuiated with exopoiymeric substances of non-protein origin (localized together] and non-encapsuiated;genus/strain/consortia-specific and typing; specific to soluble artificial polymeric polyvalent glycoconjugates imitating exposed clusters of mucin-type glycans and possessing exposed multiple carbohydrate residues such asGalNAc-alpha- or Man-alpha- as side short branches of polyacrylamide linear chain). Results indicate prospects of glycoconjugates-binding lectin systems in glycobiology, molecularglyco- medicine and bio(nano)giycotechnoiogy.